Analisis Yuridis Penerapan Restoratif Justice pada Tahap Penuntutan Terhadap Tindak Pidana Pencurian Di Bawah Nilai Dua Juta Rupiah Dalam Sistem Hukum Di Indonesia - Purba, Ahmad Rusly (Universitas Islam Sumatera Utara, 2023)
Indonesia continues to strive for laws that are implemented or lived for the community to be sourced from the values that live and develop in society, legal entities in Indonesia if applied then the community will not feel objections or unfamiliar with the legal model. Restorative justice is the resolution of criminal cases by involving perpetrators, victims, families of perpetrators / victims, and other related parties to jointly seek a fair solution by emphasizing recovery back to its original state, and not retaliation. Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General of the Republic of Indonesia states that one of the powers of the Attorney General is to set aside cases in the public interest. The AGO feels that there are many irregularities in the criminal law system that has been in effect, therefore in this case what is meant by